A study on Mexican university students: Political efficacy and social capital in online political participation (2019)
Today, the study of the influence that social media has over users’ attitudes is a line of research that is steadily growing. There are a variety of studies that have confirmed that social media makes it easier for people to express themselves both online and offline. In this article we study how the consumption of political information on social media is related to political efficacy and social capital. In order to do this, we examined the tendencies in political information consumption on social media of students from the states of Nuevo León, Sonora, Durango, and Coahuila in México. Among the main discoveries was that political efficacy is related to political participation on and off social media. © Common Ground Research Networks, Daniel Javier de la Garza Montemayor, Daniel Barredo Ibáñez, Abraham A. Hernández Paz, Some Rights Reserved